n-46=-38

Simple and best practice solution for n-46=-38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-46=-38 equation:


Simplifying
n + -46 = -38

Reorder the terms:
-46 + n = -38

Solving
-46 + n = -38

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '46' to each side of the equation.
-46 + 46 + n = -38 + 46

Combine like terms: -46 + 46 = 0
0 + n = -38 + 46
n = -38 + 46

Combine like terms: -38 + 46 = 8
n = 8

Simplifying
n = 8

See similar equations:

| (25b-7)-8(3b+1)=-6 | | 13-6(x)=11+4(x) | | 0.35x+.05(10-x)=.10(-37) | | 3=r+11 | | 5x+6x+3+9=6x+5+4x | | 1+x^3=x+7 | | 7x-8y=56 | | 11a^3+166a^2b-184ab^2-384b^3=0 | | z+13.4=-6.9 | | 5+3r-1=8r+6-4r | | -y+4y=33 | | 0.35x+.05(10-x)=.10(53) | | w+11.9=-6.2 | | (25b-4)-6(4b+3)=-3 | | 9x+5x+4+9=7x+4+6x | | o=6a^2*5 | | 1+x^3=15+x | | 6x+1=(x-22) | | -2((16)+1)+3(16)=14 | | ln(2x+9)=0 | | 9+14s-8=9s+109-7s | | 13-9(x)=11+7(x) | | 3x(x-5)+7(x-5)=0 | | 0.7w-0.3w+0.1w=2 | | x-33=-16 | | 10=8(3(22)-4)-23(22)+20 | | y=3x^2+2x-1 | | -5x^2+6x-1=0 | | 9x^2-5=0 | | g(n)=17n^3-13n^2+10n+2000 | | x=17x^3-13x^2+10x+2000 | | T(n)=17n^3-13n^2+10n+2000 |

Equations solver categories